EFEKTIVITAS MEDIA SOSIAL SEBAGAI PROMOSI UMKM DI ERA PANDEMIC COVID -19 DI DESA BATUBULAN KABUPATEN GIANYAR - I Made Sudarsana; Ni Luh Putu Trisdyani; Komang Ary Pratiwi (UNHI Press, 2021)
Batubulan Village is one of the areas located in Gianyar Regency, Bali. The community and the potential of the area are famous for their various arts crafts so that the potential of the local community has a major influence on the contribution of tourism in Bali. The onslaught of the COVID-19 pandemic that has hit the world in recent years has had an impact on all sectors, especially in Batubulan Village, which dominates its tourism activities. This incident became another stretch in the UMKM sector with all businesses that were considered new, of course, they needed social media as a promotional medium on a regular basis in order to increase UMKM buying and selling transactions. The problem is how to use social media as a means of promoting UMKM? The output target to be achieved in this research is published in the Sewaka Bhakti Journal, UNHI Denpasar, Denpasar. This research is a type of quantitative research, seen from the level of explanation. This research is an associative study with a causal relationship. To answer all the research objectives, the analysis used was Simple Linear Regression Analysis Model and to test the significance used the test. The research data analysis technique used simple regression